Therapeutic Potential of Tpl2 (Tumor Progression Locus 2) Inhibition on Diabetic Vasculopathy Through the Blockage of the Inflammasome Complex. Issue 1 (January 2021) - Sheu, Wayne Huey-Herng; Lin, Keng-Hung; Wang, Jun-Sing; Lai, De-Wei; Lee, Wen-Jane; Lin, Fu-Yu; Chen, Po-Hsun; Chen, Cheng-Hsu; Yeh, Hsiang-Yu; Wu, Sheng-Mao; Shen, Chin-Chang; Lee, Maw-Rong; et al.
Abstract : Objective: Diabetic retinopathy, one of retinal vasculopathy, is characterized by retinal inflammation, vascular leakage, blood-retinal barrier breakdown, and neovascularization. However, the molecular mechanisms that contribute to diabetic retinopathy progression remain unclear. Approach and Results: Tpl2 (tumor progression locus 2) is a protein kinase implicated in inflammation and pathological vascular angiogenesis. N ε -carboxymethyllysine (CML) and inflammatory cytokines levels in human sera and in several diabetic murine models were detected by ELISA, whereas liquid chromatography–tandem mass spectrometry analysis was used for whole eye tissues. The CML and p-Tpl2 expressions on the human retinal pigment epithelium (RPE) cells were determined by immunofluorescence. Intravitreal injection of pharmacological inhibitor or NA (neutralizing antibody) was used in a diabetic rat model. Retinal leukostasis, optical coherence tomography, and H&E staining were used to observe pathological features. Sera of diabetic retinopathy patients had significantly increased CML levels that positively correlated with diabetic retinopathy severity and foveal thickness. CML and p-Tpl2 expressions also significantly increased in the RPE of both T1DM and T2DM diabetes animal models. Mechanistic studies on RPE revealed that CML-induced Tpl2 activation and NADPH oxidase, and inflammasome complex activation were all effectively attenuated by Tpl2 inhibition. Tpl2 inhibition by NA also effectively reduced inflammatory/angiogenic factors, retinal leukostasis in streptozotocin-induced diabetic rats, and RPE secretion of inflammatory cytokines. The attenuated release of angiogenic factors led to inhibited vascular abnormalities in the diabetic animal model. Conclusions: The inhibition of Tpl2 can block the inflammasome signaling pathway in RPE and has potential clinical and therapeutic implications in diabetes-associated retinal microvascular dysfunction. Abstract : Supplemental Digital Content is available in the text.